The Robson Classification as an evaluation of the cesarean section rate in the regions of Brazil and the relationship with the infant mortality rate - Miott, Nicolle Albuquerque; Vechia , Lívia Dalla; Vargas , Adriana Cunha (Seven Editora, 2023)
INTRODUCTION: Most childhood deaths are concentrated in the first year of life, above all in the first month. There is a high participation of perinatal causes such as prematurity, by which highlights the importance of factors related to pregnancy, childbirth, and postpartum, generally preventable with quality assistment healthcare. OBJECTIVE: To analyze the prevalence of cesarean section rates according to Robson's classification in each region of Brazil and relate it with infant mortality rate. METHODOLOGY: This is a quantitative, observational, cross-sectional, and descriptive study. The study involved 7,194,258 Brazilian women aged 20 to 24 years from 2012 to 2021. The study was conducted in Brazil, covering all five regions of the country: North, Northeast, Southeast, South, and Midwest. Data were electronically obtained from the Health Department (DATASUS) of the Brazilian Unified Health System (SUS) using the TABNET application. RESULTS: Our findings suggest that patients aged 20 to 24 years old who fall into group 3 of Robson's classification are the most prevalent in Brazil then the others and They are who have a highest chance of vaginal delivery). Therefore, it can be inferred that there was an option for cesarean section and not a medical indication. Regarding newborns, it is also necessary to note that in the first and second minute of life, the Apgar score with the highest occurrence was 8-10, indicating that most babies were born with good vitality. Furthermore, the most prevalent birth weight was between 3000 and 3999 grams, which, according to the Ministry of Health, indicates the ideal weight for a healthy newborn. Moreover, it is worth noting that despite the highest infant mortality rates occurring onto 0-6 days period, we can infer that something during childbirth may have contributed to this statistic, such as an incorrect indication for cesarean section. CONCLUSION: It is common knowledge that vaginal delivery offers numerous (a several) benefits to the newborn, as in terms of immunity such as for the mother during the postpartum period. DOI:https://doi.org/10.56238/sevened2023.004-046